PENGEMBANGAN ALAT EVALUASI MATERI PROGRAM LINIER DENGAN STRATEGI BLENDED LEARNING - Istiqomah Arumsari; Nurjanah Nurjanah (UJMES (Uninus Journal of Mathematics Education and Science), 2023)
This research is motivated by the existence of online and offline learning during New Normal. One of the learning strategies that approach this situation is the strategy Blended Learning. The implementation of this strategy requires learning tools, one of which is an evaluation tool that can be used with the strategy Blended Learning. The purpose of this study was to determine the validity and practicality of the linear programming material evaluation tool with Blended Learning strategy developed. The type of research used in this study is Research and Development (RD) with method of research Borg and Gall modified by Sugiyono. This research was only carried out until the seventh stage of  ten stages proposed by Sugiyono. The validation stage involves three validators involved to test the assessment instruments and evaluation media that have been developed. Based on the results of  validation, the assessment instrument and evaluation media developed were very good . The trial was conducted on six students in one of the high schools in Garut district. Students show a good response to the developed evaluation tool, so that the practicality of the evaluation tool developed is in the practical category, can be used, and doesn’t need revision.